2006
DOI: 10.2307/25065587
|View full text |Cite
|
Sign up to set email alerts
|

A new subgeneric classification for Euphorbia (Euphorbiaceae) in southern Africa based on ITS and psbA-trnH sequence data

Abstract: We use data from the internal transcribed spacer (ITS) region of the nuclear rDNA cistron and the chloroplast psbA–trnH intergenic spacer to reconstruct the phylogenetic relationships among southern African species of Euphorbia. The results indicate that major re–organization is necessary of the groupings within Euphorbia that have been recognised in the past, since most of them turn out to be polyphyletic. Furthermore, in its present circumscription, Euphorbia itself is not monophyletic, nor do the southern A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
158
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(169 citation statements)
references
References 24 publications
11
158
0
Order By: Relevance
“…Anatomically, they are characterized by absence of glandular trichomes. The present data confirmed those of Steinmann (2003), Bruyns et al (2006) and APG III (2009).…”
Section: Type Of Cortical Tissuessupporting
confidence: 92%
See 3 more Smart Citations
“…Anatomically, they are characterized by absence of glandular trichomes. The present data confirmed those of Steinmann (2003), Bruyns et al (2006) and APG III (2009).…”
Section: Type Of Cortical Tissuessupporting
confidence: 92%
“…and Synadenium (4 spp.) (Bruyns et al, 2006). Steinmann (2003), Bruyns et al (2006) and APG III (2009) works which based on molecular data consider the genus Pedilanthus as a synonym of Euphorbia and make a valid name Euphorbia tithymaloides.…”
Section: Type Of Cortical Tissuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent molecular studies (Steinmann & Porter 2002, Bruyns et al 2006, Steinmann et al 2007 showed that the genus Euphorbia is only monophyletic if numerous generic segregates of Euphorbia are included within it, such as Chamaesyce, Cubanthus, Monadenium, Pedilanthus, Poinsettia, and others. In this broad sense, Euphorbia includes at least 2 000 species, and is therefore one of the largest non-apomictic genera of flowering plants; only few genera of phanerogams include more species, e.g., Astragalus (Leguminosae).…”
mentioning
confidence: 99%